A comparison between continuous and batch processes to produce phosphatidylserine in the efficient and green aqueous‐solid system. (25th January 2019) - Li, Binglin; Wang, Jiao; Li, Jing; Zhang, Xiaoli; Yu, Wenyu; Wang, Huan; Duan, Dandan; Zhao, Binxia
Abstract : The efficient and environmentally friendly aqueous‐solid systems employed Triton‐X‐100‐modified silica as the "artificial interface" to adsorb phosphatidylcholine (PC) in purely aqueous solutions and silica‐adsorbed PC was successfully used for phospholipase D (PLD)‐mediated transphosphatidylation. Three kinds of silicas with different sizes were employed to investigate advantages and disadvantages of batch and continuous technologies for PLD‐catalyzed transphosphatidylation in aqueous‐solid systems. The highest yields of product were obtained in the batch technology, but the continuous production had the simplest operational process and highest space–time yield. After transphosphatidylation, the product adsorbed on carriers were eluted by coconut oil and used to manufacture relevant hard, soft, and micro‐capsules. Special attention has been paid to the preparation of microcapsules. Toxic solvents were completely avoided in the whole technological process including production and product packaging. © 2019 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2777, 2019.